El ala I de los astures en el ejército romano - Santos Yanguas, Narciso (Gerión. Revista de Historia Antigua, 2008)
The Ala I Asturum is in itself one of the first instances showing the contribution of Northern Peninsular native population to the Roman Imperial army, these being soldiers recruited round about the change of era and most probably trained in the camp of the legio X Gemina. Their first outpost was Dacia, from where they would subsequently march to Britannia; later returned to the front of the Danube, where the soldiers remained until they were permanently allocated in the British province. Among the military ranks in this auxiliary troops some prefects are to be found whose names appear in epigraphic documents; its final days seem to correspond to the last decades of the third century.